Phosphonium pillar[5]arenes as a new class of efficient biofilm inhibitors: importance of charge cooperativity and the pillar platform. Issue 70 (9th August 2016) - Joseph, Roymon; Kaizerman, Dana; Herzog, Ido M.; Hadar, Maya; Feldman, Mark; Fridman, Micha; Cohen, Yoram
Abstract : Inhibition of biofilm formation (MBIC50 = 0.67–1.66 μM) by pillar[5]arene congugates. Abstract : Biofilm formation, which frequently occurs in microbial infections and often reduces the efficacy of antibiotics, also perturbs many industrial and domestic processes. We found that a new class of water soluble pillar[5]arenes bearing phosphonium moieties (1, 2) and their respective ammonium analogues (3, 4) inhibit biofilm formation with IC50 values in the range of 0.67–1.66 μM. These compounds have no antimicrobial activity, do not damage red blood cell membranes, and do not affect mammalian cell viability in culture. Comparison of the antibiofilm activities of the phosphonium-decorated pillar[5]arene derivatives 1 and 2 with their respective ammonium counterparts 3 and 4 and their monomers 5 and 6, demonstrate that while positive charges, charge cooperativity and the pillararene platform are essential for the observed antibiofilm activity the nature of the charges is not.